Effects of Dietary Crude Protein and Added Zinc on Nursery Pig Growth Performance and Fecal Dry Matter - Jentry J. Squires; Payton L. Dahmer; Joel M. DeRouchey; Julian Arroyave; Katelyn N. Gaffield; Jordan T. Gebhardt; Robert D. Goodband; Joana Magoga; Mike D. Tokach; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 360 weanling pigs (DNA 241 × 600; initially 12.0 ± 0.07 lb) were used in a 42-d growth trial to determine the effects of dietary crude protein and pharmacological levels of Zn (from ZnO) on nursery pig performance and fecal dry matter. Pigs were balanced for gender, stratified into three weight categories, and randomly allotted to pens. Pens of pigs were then assigned to one of six dietary treatments in a generalized randomized block design with five pigs per pen and 12 replicate pens per treatment. The treatments were in a 3 × 2 factorial arrangement with main effects of crude protein (low, medium, high) and Zn (110 or 3,000 mg/kg). Crude protein (CP) levels were low (20.5% in phase 1; 20% in phase 2), medium (22% in phase 1; 21.5% in phase 2), and high (23.5% in phase 1; 23% in phase 2). All basal diets contained 110 mg/kg Zn from ZnSO₄ and ZnO, which was added to reach 3,000 mg/kg where applicable. Diets were fed in three phases: phase 1 (d 0 to 10), phase 2 (d 10 to 25), and a common diet was fed to all pigs during phase 3 (d 25 to 42). During phase 1 (d 0 to 10), there was a quadratic CP × Zn interaction (P = 0.035) observed for F/G, where increasing CP in low-added Zn diets did not influence F/G. However, when CP increased in diets containing 3,000 mg/kg added Zn, a quadratic response was observed (P = 0.035) with the medium CP treatment having poorer F/G compared to the low and high CP diets. During phase 1, increasing CP decreased (linear, P ≤ 0.047) ADG and ADFI, but there was no effect on F/G. During phase 2 (d 10 to 25), increasing CP tended to decrease ADFI (linear, P = 0.063), and F/G was improved (quadratic, P = 0.005) for pigs fed the medium CP diet. Pigs fed diets with added Zn had increased (P ≤ 0.033) ADG and ADFI, with no effect on F/G. For the experimental period (d 0 to 25), ADFI decreased (linear, P = 0.011) and ADG tended (linear, P = 0.100) to decrease as dietary CP increased. Feed efficiency tended (quadratic, P = 0.052) to be improved for pigs fed the medium CP diets. Pigs fed pharmacological levels of Zn had greater ADG, ADFI, and improved F/G (P ≤ 0.002) compared with those fed basal levels of Zn. During the common phase (d 25 to 42), pigs previously fed the medium CP diets had the lowest (quadratic, P = 0.018) ADG, and increasing the CP level worsened F/G (linear, P = 0.045; quadratic, P = 0.051). Pigs previously fed pharmacological levels of Zn tended (P = 0.052) to have decreased ADG, with no differences for ADFI or F/G. Overall (d 0 to 42), pigs fed the medium CP diets tended (quadratic, P ≤ 0.098) to have decreased ADG and ADFI compared with those fed low or high CP diets. No differences were observed in F/G based on CP level. Pigs fed pharmacological levels of Zn in the experimental phase tended (P = 0.066) to have greater overall ADG, with no evidence of a difference for ADFI or F/G. A Zn × day interaction was observed (P = 0.015) for fecal DM, where pigs fed pharmacological levels of Zn had increased fecal DM on d 10 (P < 0.001) and d 25 (P = 0.024), but the magnitude of improvement was greater on d 10. In summary, there was minimal evidence of interactions between dietary CP and Zn level. In phase 1, pigs had greater ADFI and ADG with low CP diets, which also tended to be observed in the overall trial period. Pharmacological levels of Zn resulted in improvements in ADG, ADFI, and F/G during the experimental period. During the common period, pigs previously fed pharmacological Zn had lower ADG, which resulted in only a tendency for improved ADG for the overall trial period, with no overall difference in ADFI or F/G.
Keywords: crude protein; fecal dry matter; nursery pig; zinc